A new species of Amusurgus (Usgmona) Furukawa from China (Orthoptera: Gryllidae: Trigonidiinae) - Liu, Hao-Yu; Chi, Li-Cheng; Shi, Fu-Ming; Zhou, Han-Tao (Zootaxa, 2015)
Amusurgus (Usgmona) excavatus Liu, Shi et Zhou, sp. nov. (China, Fujian) is described and illustrated with the male genitalia. Photos of habitus and ecological habitat are also included.